2014
DOI: 10.1177/0305735614545197
|View full text |Cite
|
Sign up to set email alerts
|

Musical communication, emotion regulation and the capacity for attention control: A theoretical model

Abstract: In music psychology, studies of emotion regulation are typically about the self-regulation of emotion in, primarily, music listeners. What is missing from the literature is a model of emotion regulation that accounts for both intrinsic (self-generated) and extrinsic (other-generated) processes, which could inform an understanding of how music can be used by one person to extrinsically influence emotion regulation in another. To address this gap, the present article develops a theoretical model of musical commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…When learners try something beyond what they know, this could heighten their emotional stress, perhaps hindering their learning process. Although Swaine (2014) suggests that through physical coregulation with a teacher, emotional responses of learners can be regulated in ways that it enhances rather than diminishes their attentional capacity, little research has yet been done in instrumental and vocal education to explore this topic. More research into the role of the music's teacher body in instrumental and vocal education, holds the possibility to challenge, expand and refine the preliminary concept we have presented here.…”
Section: Resultsmentioning
confidence: 99%
“…When learners try something beyond what they know, this could heighten their emotional stress, perhaps hindering their learning process. Although Swaine (2014) suggests that through physical coregulation with a teacher, emotional responses of learners can be regulated in ways that it enhances rather than diminishes their attentional capacity, little research has yet been done in instrumental and vocal education to explore this topic. More research into the role of the music's teacher body in instrumental and vocal education, holds the possibility to challenge, expand and refine the preliminary concept we have presented here.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the overriding of prepotent response tendencies has been found to deplete energetic resources and to diminish the capacity for subsequent acts of self-control (e.g. acts of attention control, emotion suppression or impression management: see Baumeister, Vohs, & Tice, 2007), listening to affectmatching music may be less resource-depleting (that is, less 'effortful') than listening to affect-mismatching music, which would enable more resources to be devoted to subsequent tasks requiring self-control (presumably, each of the cognitive tasks we used in the experiments required self-control in the form of attention control) (see Swaine, 2014). These ideas may help to explain why preferences for music are directed to pieces that are emotionally congruent with a listener's internal state (Thoma et al, 2012; see also response synchronization: Scherer, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…a therapist) influences the emotion regulation strategies employed by another (e.g. a client) (see Swaine, 2014, for a discussion of this point).…”
mentioning
confidence: 99%
“…The theme 'Curriculum in relation to rhythm skills of preschoolers' demonstrated that most of these teachers employed a developmental curriculum and could become 'living curriculum material' as they adapted the difficulty of a rhythm activity on the spot to the musical level of preschoolers and to their emotional state to keep them concentrated. Possibly, through performing rhythm activities faster or slower, teachers are able to regulate excited or inattentive behaviour of preschoolers and thereby enhance their attentional capacity (Swaine, 2014).…”
Section: The Content Of Pckmentioning
confidence: 99%